Textile attributes of the fibre of Huacaya white and coloured alpacas (Vicugna pacos) from the livestock fair of south Peru - Quispe Coaquira, Jesús E. (2021)
The fibres of white (n = 143) and coloured (n = 100) Huacaya alpacas participating in the LVIII Livestock Fair of Southern Peru (FEGASUR) were characterized. The fibres were processed in the Fibre Laboratory of the Puno Regional Government. The frequencies were described under a fixed effects model (p <0.05). The frequency distributions of the fibre attributes differ from the normal curve to a different degree and depending on the variable, except for the Comfort Factor (CF), they show a tail bias to the right; being moderate the asymmetry of the Mean Diameter (MD) and slight asymmetry of the Index of Curvature (IC). Meanwhile, the dispersion variables, CF and Fibre length (LM) presented very asymmetric curves. White fibres show greater fineness than coloured fibres (p<0.05), without differences for the sex factor. The standard deviation of the mean diameter [SD (DM)] and the Coefficient of variation of the mean diameter [CV (DM)] of the white fibres had lower dispersion (p<0.05), while the CF and IC presented better values (p<0.05). The LM did not show differences between white and coloured fibres. The attributes, depending on the category of the alpacas, are related to age, except for CV(DM). It is concluded that the Huacaya alpacas of the breeding stock, white or coloured, differ from each other and are peculiar with respect to the reports that do not typify the type of herd.